Analysis of the Implementation of the e-Primary Health Center Application in Improving Primary Health Center Performance in Merangin District - Fajar Lestari; Asparian Asparian; Herwansyah Herwansyah; Dwi Noerjoedianto; Muldiasman Muldiasman; Willia Novita Eka Rini (Rifa'Institute, 2026)
Introduction: Digital health information systems are a key strategy for improving the quality and efficiency of primary health care services. Objective: This study aimed to analyze the implementation of the e-Puskesmas application in improving Primary Health Center performance in Merangin District. Methods: A qualitative study with an exploratory design was conducted through in-depth interviews, observations, and document reviews involving informants from the district health office and selected primary health centers. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, supported by triangulation techniques. Results and Discussion: The implementation of e-Puskesmas was supported by human resources, infrastructure, financial allocation, and policy support from the district health office. The application contributed to improving efficiency in data recording, timeliness of reporting, and management of health service information. However, several challenges remained, including inconsistent communication, limited resources, workload due to dual systems, unstable internet connectivity, and variations in digital literacy among health workers. Conclusions: The e-Puskesmas application has contributed to improving primary health center performance; however, optimization requires strengthening human resources, infrastructure, and data governance, as well as enhancing technical support to ensure sustainable implementation